Pathogenic role of immune cells in rheumatoid arthritis: Implications in clinical treatment and biomarker development - Yap, Hooi Yeen *; Tee, Sabrina Zi Yi *; Wong, Magdelyn Mei Theing *; Chow, Sook Khuan *; Peh, Suat Cheng *; Teow, Sin Yeang * (MDPI, 2018)
Rheumatoid arthritis (RA) is a chronic, autoimmune, systemic, inflammatory disorder that affects synovial joints, both small and large joints, in a symmetric pattern. This disorder usually does not directly cause death but significantly reduces the quality of life and life expectancy of patients if left untreated. There is no cure for RA but, patients are usually on long-term disease modifying anti-rheumatic drugs (DMARDs) to suppress the joint inflammation, to minimize joint damage, to preserve joint function, and to keep the disease in remission. RA is strongly associated with various immune cells and each of the cell type contributes differently to the disease pathogenesis. Several types of immunomodulatory molecules mainly cytokines secreted from immune cells mediate pathogenesis of RA, hence complicating the disease treatment and management. There are various treatments for RA depending on the severity of the disease and more importantly, the patient’s response towards the given drugs. Early diagnosis of RA and treatment with (DMARDs) are known to significantly improve the treatment outcome of patients. Sensitive biomarkers are crucial in early detection of disease as well as to monitor the disease activity and progress. This review aims to discuss the pathogenic role of various immune cells and immunological molecules in RA. This review also highlights the importance of understanding the immune cells in treating RA and in exploring novel biomarkers.